Rain, Agriculture, and Tariffs - Bastos, Paulo; Straume, Odd Rune; Urrego, Jaime A. (World Bank, Washington, DC, 2013)
This paper examines whether and how rainfall shocks affect tariff setting in the agricultural sector. In a model of strategic trade policy, the authors show that the impact of a negative rainfall shock on optimal import tariffs is generally ambiguous, depending on the weight placed by the domestic policy maker on tariff revenue, profits and the consumer surplus. The more weight placed on domestic profits, the more likely it is that the policy maker will respond to a rainfall shortage by reducing import tariffs. These findings are robust to alternative assumptions about market structure and the timing of the game. Using detailed panel data on applied tariffs and rainfall for 70 nations, the authors find robust evidence that rainfall shortages generally induce policy makers to set lower tariffs on agricultural imports.